The cocoa value chain in Ecuador: proposal of strategies to support sustainability (Bioagro, 2020)
The sustainable development of the agri-food sector is a priority in public-private agendas of Ecuador. A substantial amount of research has focused solely on agronomic and environmental factors. However, the research perspective must be more comprehensive. Aspects such as socio-economic performance and the level of coordination between actors require more considerable attention since they will encourage proposals for sustainable strategies. The objective of this study is to analyze the socio-economic and governance components to understand the sustainability performance of the cacao chain (Theobroma cacao) and to present potential strategies. The analysis applies a framework oriented to review of primary and support activities: the research clusters levels of pre-production, production, and post-production. Besides, it performs the mapping of the food chain, the identification of the actors, and the application of surveys to identify strengths and weaknesses. The results indicate several viable long-term strategies, such as the revision of national regulations to support small producers and the stimulation of the empowerment of young producers and associations. The main contribution of the research is the governance analysis to evaluate performance comprehensively.
Keywords: Extension programs; principal component analysis; rural development; Theobroma cacao